STUDENT INVESTMENT DECISIONS USING SHARIA MUTUAL FUND PRODUCTS VIA DIGITAL INVESTMENT PLATFORM - Siti Rafifa Nabila; Hilda Monoarfa; Suci Apriliani Utami (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2024)
Looking at the influence of sharia financial literacy, return expectations, perceived convenience, and perceived benefits on students' investment decisions using sharia mutual fund products through digital investment platforms. The method used is a quantitative approach, descriptive causality design with the Partial Least Square-Structural Equation Modeling (PLS-SEM) analysis tool with the help of the SmartPLS 4 application. The results of this research descriptively show that the level of return expectations, the level of perceived convenience, and the level of perceived benefits are in the high category and the level of sharia financial literacy is in the medium category. In addition, the hypothesis results show that the level of sharia financial literacy, return expectations, perceived convenience, and perceived benefits have a significant positive effect on students' investment decisions using sharia mutual fund products through digital investment platforms.